Identifying Core Personality Predictors of Psychophysiological Health Outcomes - Sayedalitabar, Sayed Hadi; Goli , Farzad; Goli , Ava (Journal of Personality and Psychosomatic Research (JPPR), 2026)
This study aimed to explore how stable personality traits, particularly conscientiousness and neuroticism, influence psychophysiological health outcomes through emotional regulation, behavioral patterns, and cognitive–affective integration among adults in Canada. This qualitative study employed a descriptive–exploratory design to examine the lived experiences of individuals regarding the interaction between personality and psychophysiological well-being. Twenty-one adult participants (11 women, 10 men) aged 25–55 from various provinces in Canada were selected using purposive sampling. Data were collected through semi-structured interviews, each lasting 60–90 minutes, and analyzed using thematic analysis in NVivo 14 software. Sampling continued until theoretical saturation was achieved. The analytic process followed Braun and Clarke’s six-step framework, including open and axial coding to derive major themes. Credibility was ensured through member checking and peer debriefing. Three major themes emerged from the data: (1) Emotional Regulation and Stress Reactivity, capturing the link between personality traits, emotion control, and physiological stress responses; (2) Personality Dispositions Influencing Health Behavior, emphasizing conscientiousness and neuroticism as primary determinants of health-promoting or risk behaviors; and (3) Cognitive–Affective Integration and Meaning Construction, illustrating how mindfulness, meaning in life, and self-reflection mediate personality’s effect on physiological well-being. Participants high in conscientiousness reported adaptive coping, lower stress reactivity, and greater resilience, while those with high neuroticism experienced more psychosomatic symptoms but sometimes converted anxiety into health vigilance—reflecting the “healthy neuroticism” effect. Personality traits, particularly conscientiousness and neuroticism, are central predictors of psychophysiological health. Their interaction shapes emotional regulation, behavioral consistency, and physiological adaptation.